Examples of incorrect mathematics in Lithuanian textbooks - Norvaiša, Rimas (Lietuvos matematikos rinkinys, 2025)
The article discusses the cases of incorrect mathematics in textbooks. For example, instead of defining of a mathematical concept,textbooks explain mathematical symbols and terms. In other cases, false or non-trivial facts are used to justify or prove statements as if they were self-evident. We also provide examples of logical reasoning errors. We explain some cases of incorrect mathematics in textbooks by the problematic nature of mathematics syllabus. Other cases of incorrect mathematics arises from the different treatment of the same topics in different textbooks. In all the cases discussed, we offer alternative correct solutions.
Keywords: content of school mathematics; mathematics textbooks; correct mathematics; definition; proof